DESCRIPTION OF AUTHENTIC ASSESSMENT IN ENGLISH LEARNING TO THE RURAL JUNIOR HIGH SCHOOL IN TABANAN REGENCY - Gusti Ayu Gede Sukraningsih (FAKULTAS PENDIDIKAN BAHASA DAN SENI IKIP SARASWATI, 2020)
Learning assessment is important aspect in valuing education achievement. In line with this, the Ministry of Education and Culture issues minister of education and culture regulation No. 23 Year 2016 (Permendikbud No 23 Year 2016) governing the standard of assessment, one of which is authentic assessment. This research aimed at describing authentic assessment in English learning toward the students of two rural state schools in Tabanan regency, namely SMP Negeri 1 Kerambitan and SMP Negeri 2 Kediri. The subjects of this research were five teachers and 155 students. The techniques of data collection used in this research were observation, interview, and documentation. The data were analyzed by using qualitative data analysis consisting of data reduction, data display, conclusion, and verification. Based on the analysis, it was found that (1) the authentic assessment was implemented in learning process by assessing the competence of attitude, knowledge, and skills. (2) the techniques of assessment used to value each competency include (a) observation and journal for attitude competency, (b) written test, oral test, and assignment for knowledge competency, and (c) performance, project, and portfolio for skills competency. The conclusion of this research is the authentic assessment in both schools is well implemented. It is due to the efforts of the local government through Department of Education and each school to hold the training program to the teachers on curriculum 2013 implementation.